Developing a City Scale Emissions Inventory and Exploring Electrification of Transportation: A Case Study of the City of Waterloo - Rana, Isha (University of Waterloo, 2020)
Significant growth in the scale of climate action is witnessed globally as cities, nations and environment agencies implement mitigation strategies and try to meet their ambitious emission reduction goals. As a result, many sectors have experienced significant emission reduction in recent years, except for transportation. Over the past two decades, transportation emissions, primarily driven by the sector’s high dependency on fossil fuels, are continuously rising. Cities are the hotspots as they drive the majority of transportation demand. Various policies and local climate action strategies are already in place to mitigate emissions, including but not limited to reducing auto dependency and the use of alternative modes and cleaner fuel. However, limited means are available to quantify the effectiveness of these strategies. While various methods and guidelines inform national emission estimation processes, limited tools are available for cities to report their local emission inventory. The purpose of this research, therefore, is to prepare a methodology which can be adopted by local authorities to better report and manage local transport emissions at the municipal and regional scale. The Environmental Protection Agency’s (EPA) Motor Vehicle Emission Simulator (MOVES) is customized to develop emissions inventory at the disaggregated level while capturing local transportation characteristics. The model is applied to a case study area selected in the City of Waterloo, and emissions (CO2 equivalent) are estimated from different vehicle types and vehicle activities. The emission results obtained are extrapolated to the city scale, and different scenarios are explored to identify the potential for Electric Vehicles (EVs) to contribute to further emission reduction. Transportation sector emissions for the City of Waterloo are projected for 2031 and 2051 based on increased traffic and commercial vehicle activity share. Research findings suggest that the majority of Waterloo’s transportation sector emissions are from light-duty vehicles. Heavy and medium-duty vehicles, on the other hand, have a smaller share in total vehicle activity but are significant contributors to emissions, which makes their electrification critical to the City’s emission reduction plan. To meet the City’s long-term emission reduction goals, an ideal transport emissions profile is created considering the complete and partial electrification of different vehicle types. The research findings suggest that to achieve the City of Waterloo’s 2050 emission reduction target, 100% electrification of light and medium-duty vehicles and 25% electrification of heavy-duty vehicles would be required. However, this transition to an electric fleet is quite challenging as economic, policy and infrastructure barriers to market adoption of electric vehicles, especially medium and heavy-duty vehicles need to be addressed.
Keywords: emissions; freight; electric vehicle; urban transport emissions; emissions model; microscopic emissions model; urban transport